(untitled) (Altre Modernità, 2016)
Access from the political left to power in various Latin American countries also seemed to announce adherence to government policies by intellectuals linked ideologically to progressivism, especially after the escalation of repression that followed the Cuban revolution. Today notes, however, a growing gap between making political demonstrations of the intelligentsia and government teams that should represent them. That disaffection comes together with a rise of the opposition of social movements in different national contexts and with a media transformation of social relations, which seems to intensify the dismantling of modern subjectivity. Chile and Uruguay in recent years provide significant examples of these trends, the effect in turn of a general crisis of modern organic nature in society.